The Underdog Effect: The Marketing of Disadvantage and Determination through Brand Biography - Paharia, Neeru; Keinan, Anat; Avery, Jill; Schor, Juliet B. (Journal of Consumer Research, 2011)
We introduce the concept of an underdog brand biography to describe an emerging trend in branding in which firms author a historical account of their humble origins, lack of resources, and determined struggle against the odds. We identify two essential dimensions of an underdog biography: external disadvantage, and passion and determination. We demonstrate that such a biography can increase purchase intentions, real choice, and brand loyalty. We argue that these biographies are effective because consumers react positively when they see the underdog aspects of their own lives being reflected in branded products. Four studies demonstrate that the underdog brand biography effect is driven by identity mechanisms: we show that the effect is (a) mediated by consumers' identification with the brand, (b) greater for consumers who strongly self-identify as underdogs, (c) stronger when consumers are purchasing for themselves versus for others, and (d) stronger in cultures in which underdog narratives are part of the national identity.